The Effect of Entrepreneurial Passion and Entrepreneurial Education on Entrepreneurial Intention through Entrepreneurial Mindset among Students at Universitas Negeri Surabaya - Krista Suci Reffandi; Waspodo Tjipto Subroto; Dwi Yuli Rakhmawati; Shih-Wen Liu (JURNAL EKONOMI PENDIDIKAN DAN KEWIRAUSAHAAN, 2026)
Objective: This study aims to analyze the effect of entrepreneurial passion and entrepreneurial education on entrepreneurial intention through entrepreneurial mindset among students at university. Method: This study used a quantitative approach, with an explanatory research design. The sampling technique used was non-probability sampling. The respondents were 252 students from Universitas Negeri Surabaya. Data analysis used Partial Least Squares–Structural Equation Modeling (PLS-SEM), which includes testing the outer model, inner model, and hypothesis.  Results: The results of the study show that entrepreneurial passion and entrepreneurial mindset significantly influence entrepreneurial intention, while entrepreneurial education has no direct effect on entrepreneurial intention. Furthermore, entrepreneurial passion and entrepreneurial education significantly influence the entrepreneurial mindset. The results of the mediation test indicate that the entrepreneurial mindset can mediate the influence of entrepreneurial passion and entrepreneurial education on entrepreneurial intention.  Novelty: This study provides a theoretical contribution in expanding the study of the Theory of Planned Behavior (TPB) in forming perceived behavioral control through an entrepreneurial mindset to create entrepreneurial intentions among students in developing countries.